EVALUASI PEMBELAJARAN DALAM KONTEKS FUNGSI, TUJUAN DAN MANFAAT YANG DILAKUKAN OLEH PENDIDIK (Telaah Evaluasi Pembelajaran dalam Mapel Pendidikan Agama Islam) - Shoheh, Moh; Ahmad, Ahmad (AHSANA MEDIA: Jurnal Pemikiran, Pendidikan dan Penelitian Ke-Islaman, 2019)
Evaluation of learning is a must done by the teacher or educator. This is done as a result of the learning process for 1semester, which is accumulated starting from daily tests, uts and uas. In this case also the educator needs to know aboutthe function, purpose and benefits of the assessment. So it is not selective in giving assessments to students, andstudents are not disadvantaged in providing such assessments. Problem formulation 1) What is meant by evaluation oflearning in the context of functions, objectives and benefits? 2) How are the learning evaluation techniques carried outby educators to their students? With the aim of describing evaluation of learning in the context of functions, objectivesand benefits. and analyze learning evaluation techniques carried out by educators to their students.